2018
DOI: 10.1089/lap.2017.0518
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Hepatic Resection for Solitary Hepatocellular Carcinoma Less Than 5 cm in Cirrhotic Patients: A Randomized Controlled Study

Abstract: LLR is superior to the OLR with significantly shorter duration of hospital stay and does not compromise the oncological outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 47 publications
5
35
0
5
Order By: Relevance
“…It was different from overall survival (p = 0.03) but not different from disease-frees survival (p = 0.2). This indicates that the long-term e cacy of laparoscopic hepatectomy is basically equivalent to that of open hepatectomy, which is basically consistent with the conclusions of other scholars [19][20][21] .…”
Section: Discussionsupporting
confidence: 89%
“…It was different from overall survival (p = 0.03) but not different from disease-frees survival (p = 0.2). This indicates that the long-term e cacy of laparoscopic hepatectomy is basically equivalent to that of open hepatectomy, which is basically consistent with the conclusions of other scholars [19][20][21] .…”
Section: Discussionsupporting
confidence: 89%
“…LLR had comparative resection time (66.56 ± 23.80 min vs. 59.56 ± 14.74 min, P = 0.218), amount of blood loss (250 mL vs. 230 mL, P = 0.915), transfusion rate (P = 1.00), and R0 resection rate when compared with OLR. There was no significant difference between the two groups in terms of postoperative tumor-free survival time [33] . In a Japanese study, information on patients undergoing liver cancer surgery was collected from 31 centers between 2000 and 2010, and divided into LLR (n = 436) and OLR (n = 2969) groups.…”
Section: Laparoscopic Hepatectomymentioning
confidence: 71%
“…However, there is no evidence that patients with liver cancer who undergo laparoscopic liver resection are afforded a better prognosis. In a recent study, Ahmed El-Gendi et al [33] compared the therapeutic effects of OLR with LLR in patients with liver cirrhosis (Child A) with solitary small (< 5 cm) peripheral HCC. The results showed that LLR had significantly less operative time (120.32 ± 21.58 min vs. 146.80 ± 16.59 min, P < 0.001) and shorter duration of hospital stay (2.40 ± 0.58 days vs. 4.28 ± 0.79 days, P < 0.001), with comparable overall complications (25% vs. 28%, P = 0.02).…”
Section: Laparoscopic Hepatectomymentioning
confidence: 99%
“…First experiences in laparoscopic liver resections for HCC go back over 20 years as reported by Daniel Cherqui in a feasibility study in 30 patients [28]. Meanwhile there is one controlled randomized study (n = 25 vs. n = 25) comparing laparoscopic and open liver resection in early HCC (< 5 cm) in compensated cirrhosis (CHILD A) from Egypt [29]. Operative time and hospital stay were decreased in the laparoscopic group with otherwise comparable perioperative results.…”
Section: Hepatocellular Carcinoma and Liver Cirrhosismentioning
confidence: 97%